Peningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Kooperatif Tipe STAD Siswa Kelas III SDIT AL Iman - Anisa Prihatini; Ayu Ratna Wulandari; Muhammad Arif (Kilau Publishing, 2023)
The problem that is the focus of the study in improving learning is the low learning outcomes of class III students in science lessons at SDIT AL IMAN, where the average value of learning outcomes is still below the KKM so a new learning model is needed. The aim of learning improvement research is to describe the application of a realistic approach to improving Mathematics learning outcomes regarding simple fractions. This research was carried out in October - November 2023 at SDIT AL IMAN, with research subjects totaling 30 students. The design of this learning improvement procedure uses classroom action research which consists of two cycles and each cycle includes four stages, namely planning, implementation, observation and reflection. The results of the pre-cycle research were 12 (40%) students who had not completed it. Then, there was an increase in learning outcomes in cycle I as many as 20 (67%) students reached the KKM, likewise in cycle II, the scores of students who reached the KKM were 27 (90%) students. It can be concluded that the STAD type cooperative learning model can improve learning outcomes Science students on animal life cycle material.